2009
DOI: 10.1111/j.1750-3841.2009.01106.x
|View full text |Cite
|
Sign up to set email alerts
|

Extraction and Physicochemical Characterization of Greater Lizardfish (Saurida tumbil) Skin and Bone Gelatin

Abstract: Type A gelatins were extracted from skins and bones of lizardfish and analyzed to determine their functional and chemical properties. Lizardfish skin gelatin had ash content of 2.2 +/- 0.3% while bone gelatin had ash content of 12.2 +/- 0.2%. Gel strength was 159.1 +/- 14 and 135 +/- 7.9 g, respectively, for skin and bone gelatins compared to 224.3 +/- 7.7 g for porcine gelatin. Gelatin from skin exhibited higher viscosity and lower setting time than bone. Skin gelatin had higher imino acid content than bone g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(34 citation statements)
references
References 24 publications
2
32
0
Order By: Relevance
“…The amino acid compositions found in the garfish periosteum and spinal processes were almost identical. Comparison with the literature [21][22][23] shows good agreement with the amounts of individual amino acids in fish connective tissue from bone. Further, comparison with the amounts of the amino acids hydroxyproline and proline shows that the periosteum and the protein of the spinal processes chiefly consist of collagen.…”
Section: Concentrationsmentioning
confidence: 77%
“…The amino acid compositions found in the garfish periosteum and spinal processes were almost identical. Comparison with the literature [21][22][23] shows good agreement with the amounts of individual amino acids in fish connective tissue from bone. Further, comparison with the amounts of the amino acids hydroxyproline and proline shows that the periosteum and the protein of the spinal processes chiefly consist of collagen.…”
Section: Concentrationsmentioning
confidence: 77%
“…A large amount of skin was used to extract gelatins, including bigeye snapper ( Priacanthus macracanthus ) ), bigeye snapper ( Priacanthus tayenus ) (Sukkwai et al 2011 ), bigeye snapper ( Priacanthus hamrur ) (Binsi et al 2009 ), cuttlefi sh ( Sepia pharaonis ) (Aewsiri et al 2009 ), greater lizardfi sh ( Saurida tumbil ) (Taheri et al 2009 ), hoki ( Macruronus novaezelandiae ) (Mohtar et al 2011 ), blacktip shark ( Carcharhinus limbatus ), and giant catfi sh ( Pangasianodon gigas ) (Jongjareonrak et al 2010 ). Others species that have been studied as a source of gelatin include coldwater fi sh like, cod, Atlantic salmon, haddock, Alaska pollock, or hake, tropical or subtropical species, for example black or red tilapia, Nile perch, yellowfi n tuna, channel catfi sh, sin croaker, shortfi n scad, grass carp, and skate, and fl at species like megrim and Cephalopods species like giant squid (Aberoumand 2012 ;Aewsiri, et al 2009 ;Benjakul et al 2009 ;Binsi et al 2009 ;Jongjareonrak et al 2010 ;Mohtar et al 2011 ;Taheri et al 2009 ;Zúñiga and Aguilera 2009 ;Zhou et al 2006 ).…”
Section: Gelatin Production From Fishmentioning
confidence: 99%
“…It was probably due to the degradation of α-and β-chains by endogenous proteinase during extraction. The presence of protein degradation fragments may reduce the ability of α-chains to anneal correctly during stabilization overnight and thus hindering the growth of the existing nucleation sites (Ledward, 1986;Normand et al, 2000;Taheri et al, 2009). Benjakul et al (2012) reported that gelatin molecules with the shorter chains generated by endogenous proteinase are not able to form the strong inter-junction zone, especially via hydrogen bond or other weak bonds such as hydrophobic interaction or ionic interaction.…”
Section: Gel Strength Of Gelatin Gelmentioning
confidence: 99%